High erythropoietin levels are associated with low neurofilament light levels in simulated high altitude: a further hint for neuroprotection by erythropoietin - Berek, Klaus; Berek, Anna; Bauer, Angelika; Rudzki, Dagmar; Di Pauli, Franziska; Bsteh, Gabriel; Ponleitner, Markus; Treml, Benedikt; Kleinsasser, Axel; Berger, Thomas; Wille, Maria; Burtscher, Martin; et al. (Frontiers in neurology, 2025)
Erythropoietin (EPO) plays a crucial role in the early adaption to high altitude and is possibly involved in neuroprotection. Neurofilament light chain (NfL) is an established marker of neuroaxonal damage. To investigate whether EPO dynamics in simulated high altitude are linked to neuroaxonal damage as measured by NfL. Sixty-three healthy subjects were exposed to simulated altitude of 4,500 m for 12 h in a normobaric hypoxic chamber at the University of Innsbruck. Clinical data (heart rate, arterial oxygen saturation) were assessed before and 3 h after high altitude exposure; plasma samples were drawn before (measurement (M) 1) and after 12 h (M2). The levels of EPO and hypoxia-inducible factor (HIF)-1α were quantified using commercially available ELISA kits. NfL concentrations were measured using the Simoa SR-X Analyzer, and NfL Z scores calculated using age- and body mass index (BMI)-adjusted reference values. EPO significantly increased after 12 h (M2: 10.12 [7.86-14.06] mU/mL vs. M1: 4.17 [2.99-5.67] mU/mL, < 0.001), while HIF-1α did not significantly change ( = 0.409). Subjects with high EPO levels at M2 showed significantly lower NfL concentrations (5.85 [4.15-6.85] pg/mL vs. 6.73 [4.70-8.64] pg/mL, = 0.030) as well as lower NfL Z scores (0.64 [-0.88-1.17] vs. 0.95 [0.25-1.48], = 0.040) than those with low EPO levels. The extent of heart rate increase showed a positive correlation with EPO levels at M2 (r = 0.322, = 0.011). Higher EPO concentrations were associated with lower NfL levels. This might further substantiate the hypothesis of a neuroprotective role of EPO.